THE INFLUENCE OF MACROECONOMIC AND MICROECONOMIC VARIABLES ON STOCK PRICE FLUCTUATIONS - Sasi, Maria Ketty; Ballo, Fransina W; Bolang3, Rikhard T Ch (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to determine the effect of macroeconomic factors including the Exchange Rate and Money Supply, and microeconomic factors including Cash Dividend Rate, Stock Trading Volume, and Earning Per Share on stock price fluctuations in Financial sector companies in the banking sub-sector listed on the Indonesia Stock Exchange. This study uses a panel data model analysis with a time period used of 2019-2023. The population in this study were 21 banking sub-sector companies which are conventional banks and have made cash dividend payments during the study period. The research sample used was 6 banking sub-sector companies that had met the criteria set in this study. This study uses the Common Effect Models (CEM) panel data model. The results of this study indicate that the exchange rate and earning per share variables affect stock price fluctuations, while the money supply, cash dividend rate, and stock trading volume variables do not affect stock price fluctuations. Meanwhile, the exchange rate and earning per share variables affect stock price fluctuations.